2017
DOI: 10.4183/aeb.2017.519
|View full text |Cite
|
Sign up to set email alerts
|

Novel Markers for Early Diagnosis and Prognostic Classification in Medullary Thyroid Carcinoma

Abstract: Medullary thyroid carcinoma is a neuroendocrine tumour of the parafollicular C cells of the thyroid gland. It is an aggressive tumor that can be cured only by complete resection of the thyroid tumour and any local and regional metastases. Thus, the discovery of novel diagnostic and prognostic markers is very important for early diagnosis and correct management, in order for the survival rates to rise. New research has emphasized the potential role of various genes, serum and immunohistochemical markers, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Measurement of serum calcitonin has been used as an important tumor marker in patients with MTC. However, consensus on its role in the evaluation of a thyroid nodule remains elusive [ 20 ]. Studies have reported negative calcitonin in nonsecretory MTC [ 21 ], indicating that normal serum calcitonin does not exclude the presence of MTC [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of serum calcitonin has been used as an important tumor marker in patients with MTC. However, consensus on its role in the evaluation of a thyroid nodule remains elusive [ 20 ]. Studies have reported negative calcitonin in nonsecretory MTC [ 21 ], indicating that normal serum calcitonin does not exclude the presence of MTC [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemoembolization with adriamycin may be efficient in large liver metastases. Kinase inhibitors of tumor cells (RET and other kinases) or of endothelial cells (VEGFR) such as Cabozantinib or Vadentanib may be efficient in selected cases of progressive disease and should be used as first line intention (22,23). MTC is an immunologically active tumor and has a specific immune profile which may be therapeutically targeted.…”
Section: Novelties In the Medical Therapy For Mtcmentioning
confidence: 99%
“…There are even controversies about CT measurement in the screening of a thyroid nodule/polynodular goitre. Despite the fact that American Thyroid Association (ATA) has not disclosed a statement for or against CT measurement in thyroid nodule(s) screening, some authors have stressed out that CT dosage is important for an early diagnosis of MTC [2][3][4][5][6][7][8]. More than that, some studies reported that CT dosage has a greater diagnostic sensitivity and specificity than FNAB [1,9].…”
Section: Introductionmentioning
confidence: 99%